Marronage, Here and There: Liberia, Enslavement’s Conversion, and the Settler-Not - Woods, Tryon P. (International labor and working class history, 2019)
This proposed contribution to the special issue of ILWCH offers a theoretical re-consideration of the Liberian project. If, as is commonly supposed in its historiography and across contemporary discourse regarding its fortunes into the twenty-first century, Liberia is a notable, albeit contested, instance of the modern era’s correctable violence in that it stands as an imperfect realization of the emancipated slave, the liberated colony, and the freedom to labor unalienated, then such representation continues to hide more than it reveals. This essay, instead, reads Liberia as an instructive leitmotif for the conversion of racial slavery’s synecdochical plantation system in the Americas into the plantation of the world writ large: the global scene of antiblackness and the immutable qualification for enslavement accorded black positionality alone. Transitions between political economic systems—from slave trade to “re-colonization,” from Firestone occupation to dictatorial-democratic regimes—reemerge from this re-examination as crucial but inessential to understanding Liberia’s position, and thus that of black laboring subjects, in the modern world. I argue that slavery is the simultaneous primitive accumulation of black land and bodies, but that this reality largely escapes current conceptualization of not only the history of labor but also that of enslavement. In other words, the African slave trade (driven first by Arabs in the Indian Ocean region, then Europeans in the Mediterranean, and, subsequently, Euro-Americans in the Atlantic) did not simply leave as its corollary effect, or byproduct, the underdevelopment of African societies. The trade in African flesh was at once the co-production of a geography of desire in which blackness is perpetually fungible at every scale, from the body to the nation-state to its soil—all treasures not simply for violation and exploitation, but more importantly, for accumulation and all manner of usage. The Liberian project elucidates this ongoing reality in distinctive ways—especially when we regard it through the lens of the millennium-plus paradigm of African enslavement. Conceptualizing slavery’s “afterlife” entails exploring the ways that emancipation extended, not ameliorated, the chattel condition, and as such, impugns the efficacy of key analytic categories like “settler,” “native,” “labor,” and “freedom” when applied to black existence. Marronage, rather than colonization or emancipation, situates Liberia within the intergenerational struggle of, and over, black work against social death. Read as enslavement’s conversion, this essay neither impugns nor heralds black action and leadership on the Liberian project at a particular historical moment, but rather agitates for centering black thought on the ongoing issue of black fungibility and social captivity that Liberia exemplifies. I argue that such a reading of Liberia presents a critique of both settler colonialism and of a certain conceptualization of the black radical tradition and its futures in heavily optimist, positivist, and political economic terms that are enjoying considerable favor in leading discourse on black struggle today.